The Effect of Motivation and Job Satisfaction on Employee Performance at The Office of Population and Civil Registration Services of South Nias Regency - Saverius Buulolo; Afdal Rianus Zamili; Merlinda Buulolo; Sitati Halawa; Florentina Wau; Fanemali Halawa (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study aims to examine the effect of work motivation and job satisfaction on employee performance at the Department of Population and Civil Registration of South Nias Regency. The research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to all 65 employees, applying a saturated sampling technique. The research instruments were tested for validity and reliability, while data analysis was conducted using multiple linear regression with SPSS version 25. The results indicate that work motivation has a positive and significant effect on employee performance. In addition, job satisfaction also shows a positive and significant influence on employee performance. Simultaneously, work motivation and job satisfaction significantly affect employee performance. These findings suggest that higher levels of motivation and job satisfaction contribute to improved employee performance. Therefore, organizations are encouraged to enhance motivational strategies and improve job satisfaction to achieve better performance outcomes and sustainable improvements in public service quality.